2015
DOI: 10.1111/jcmm.12408
|View full text |Cite
|
Sign up to set email alerts
|

The role of the cell–cell interactions in cancer progression

Abstract: In the field of cancer research, scientific investigations are based on analysing differences in the secretome, the proteome, the transcriptome, the expression of cell surface molecules, and the deregulation of signal transduction pathways between neoplastic and normal cells. Accumulating evidence indicates a crucial role in carcinogenesis concerning not only stromal cells but also normal cells from target organs and tissue where tumours emerge. The tumour microenvironment (TME) definitively plays an important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(77 citation statements)
references
References 140 publications
(196 reference statements)
2
69
0
3
Order By: Relevance
“…A lot of evidences suggest that cancer is a disease of the genome at the cellular level (Sarkar et al, 2013). In addition, cancer development is a multistep process in which cell-to-cell communications by paracrine signaling interactions and exosome-mediated transfer of cellular contents between cancer cells and associated stromal cells are important on various aspects of carcinogenesis and its progression (Kaminska et al, 2015;Quail and Joyce, 2013;Roma-Rodrigues et al, 2014). Recent studies have also been shown TNTs may provide an alternative mechanism by which cell-to-cell signaling and cell content transfer takes place between cells in cancer microenvironment.…”
Section: Cancer Initiation and Progressionmentioning
confidence: 99%
“…A lot of evidences suggest that cancer is a disease of the genome at the cellular level (Sarkar et al, 2013). In addition, cancer development is a multistep process in which cell-to-cell communications by paracrine signaling interactions and exosome-mediated transfer of cellular contents between cancer cells and associated stromal cells are important on various aspects of carcinogenesis and its progression (Kaminska et al, 2015;Quail and Joyce, 2013;Roma-Rodrigues et al, 2014). Recent studies have also been shown TNTs may provide an alternative mechanism by which cell-to-cell signaling and cell content transfer takes place between cells in cancer microenvironment.…”
Section: Cancer Initiation and Progressionmentioning
confidence: 99%
“…Cells influence each other in two major ways: first, by indirect interaction through release of molecular signals into the free intracellular space, and, second, by direct interaction through physical cell-cell contacts, including the formation of junctions between mechanically coupled epithelial cells, synaptic connections between neurons, activation of lymphocytes by antigen-presenting cells, and infection of host cells by intracellular parasites. Malfunctions of direct cell-cell contact are associated with numerous diseases, including developmental defects, neurological disorders, immunological abnormalities, and cancers (1)(2)(3). Therefore, the ability to detect and manipulate cells that contact one another directly is fundamental to both basic and clinical research.…”
mentioning
confidence: 99%
“…Previous studies have demonstrated that the interaction between cancer cells and the stromal cells of the tumor microenvironment is required for the survival and localization of cancer cells (27)(28)(29). Recently, targeted treatments based on cytokines and adhesion molecules have been investigated, leading to improvements in the treatment of tumors and inhibition of tumor metastasis (30).…”
Section: Discussionmentioning
confidence: 99%